The Effect of Enterprise Risk Management Implementation on the Sustainable Business Performance of MSME Tapis in Bandar Lampung - Nurkasya, Muhammad Luthfi; Mahrinasari MS (InJEBA : International Journal of Economics, Business and Accounting, 2024)
The Tapis industry MSMEs in Bandar Lampung City frequently encounter challenges that hinder their survival, growth, and development. These challenges include issues related to human resource capabilities, product innovation, financing, and marketing, which impede their ability to compete, particularly against larger companies. This study aims to assess the impact of various dimensions of Enterprise Risk Management (ERM) on the performance of the creative Tapis industry in Bandar Lampung. Data for the study were collected through a questionnaire and analyzed using simple linear regression analysis, with a sample of 100 MSMEs in Bandar Lampung City. Descriptive analysis of each ERM dimension indicates that, in general, the Tapis MSMEs studied have implemented ERM practices to a satisfactory degree. The results from the simple linear regression analysis reveal a coefficient of determination of 0.191, indicating that 19.1% of the sustainable performance of Tapis MSMEs can be attributed to ERM practices. The significance level obtained is notably low at 0.001, suggesting that the implementation of ERM is effective in enhancing sustainable performance. In conclusion, Enterprise Risk Management (ERM) has a positive and significant effect on the sustainable business performance of Tapis industry MSMEs in Bandar Lampung, particularly in the dimensions of the internal environment, information and communication, and monitoring.